UJI EFEKTIFITAS BOLU KUKUS JUS BUNGA TELANG - Amelia Nirmalawaty; Anak Agung Putu Sri Mahayani (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2022)
The aim of the research was to determine the effect of adding butterfly pea flower juice to changes in its physical and chemical properties. A completely randomized design with 3 levels of butterfly pea flower juice (3, 6, and 9%) and control treatment was chosen as the experimental method. The hedonic test (taste, aroma, and color) showed the panelists' preference level which was not significantly different in taste and aroma but the addition of 6 and 9% butterfly pea flower juice resulted in a blue color favored by the panelists. The addition of butterfly pea flower juice significantly affected the dough's swellability, texture, moisture content, and fiber content. After the effectiveness test, the addition of 6% telang flower juice is the recommended treatment from the results of this research